The Effect of Implementing Enterprise Resource Planning Systems on Profitability Ratios, Activity Ratios, and Solvency Ratios of Companies - Hendra Martuah Fransiscus; Weli Weli (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Enterprise Resource Planning (ERP) is an integrated information system designed to support the management of enterprise resources such as funds, people, and materials. Although ERP is expected to improve operational performance and efficiency, its implementation often faces significant challenges related to process integration complexity, time, and cost. This study aims to examine the effect of ERP implementation on firm performance with a focus on profitability, activity, and solvency ratios after three and five years of implementation. The quantitative method was used with a sample of 29 Indonesian companies listed on the Indonesia Stock Exchange and have implemented ERP. Data was analyzed using logarithmic regression through SPSS 23.0 to compare financial performance before and after ERP implementation. The results showed that in general ERP implementation did not have a significant effect on profitability, activity, and solvency ratios in the short (3 years) and medium (5 years) terms. However, there is a significant effect on the activity ratio after five years, namely a decrease in asset turnover and an increase in labor productivity. This finding indicates that the benefits of ERP are more visible in internal efficiency and productivity improvements rather than direct changes in financial performance. In conclusion, ERP provides long-term benefits especially in operational and decision-making aspects, although the financial impact is not always immediately apparent. This study suggests the need for long-term evaluation and adjustment of business processes to maximize ERP benefits.